Pengaruh Prudence, Profit Persistence, dan Faktor Lainnya terhadap Earnings Quality - Rayhan Hutama Satyadi; Deasy Ariyanti Rahayuningsih (Media Bisnis, 2026)
The purpose of this research is to analyze the effect of firm size, current ratio, investment opportunity set, audit committee, auditor size, institutional ownership, prudence, profitability, and profit persistence on earnings quality. The population used in this study are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period, with 64 companies as samples. Sample selection using purposive sampling method, with hypothesis testing using multiple linear regression. The results showed that the independent variable profitability had a negative effect on earnings quality. High profitability does not always reflect the actual financial condition. Earnings can be manipulated to attract investors. As a result, companies with high profitability are often suspected of earnings management which reduces earnings quality. In addition, firm size, current ratio, investment opportunity set, audit committee, auditor size, institutional ownership, prudence and profit persistence have no effect on earnings quality. These findings provide important implications for both theory and practice. Theoretically, this study enriches the literature on earnings quality by highlighting that profitability may not always serve as a reliable indicator of financial reporting quality. Practically, investors are advised to be more cautious in interpreting high profitability and to consider other financial and non-financial indicators before making investment decisions. For companies, the results emphasize the importance of maintaining transparency and avoiding earnings management practices to enhance credibility. Regulators are also encouraged to strengthen monitoring mechanisms to ensure the reliability of financial reporting and protect stakeholders’ interests.